Knowledge, demand, and the need of lay people for the orthodontic specialty in comparison to other dental disciplines - Naif A Bindayel (Wolters Kluwer Medknow Publications, 2018)
OBJECTIVE: To assess the knowledge of, demand for, and need for the orthodontic specialty in comparison to other dental fields in a sample of Saudi males. MATERIALS AND METHODS: A multiple choice questionnaire was designed to assess participants' knowledge interest, demand, and need for treatment in the following dental specialties: orthodontics, periodontics, prosthodontics, endodontics, and restorative dentistry. Subjects desiring clinical examination underwent further assessment to document their actual needs. In addition to the subjects' age, the frequencies of tooth brushing, dental pain, treatment seeking, and routine checkup were collected. Descriptive statistics and Pearson's Chi-square test were applied to compare the percentages of the knowledge of, demand for, and need for each dental discipline. The significance level was set at P < 0.05. RESULTS: A total of 1566 Saudi males completed the initial survey of dental knowledge, and 1406 subjects then completed the needs checklist. For the assessment of treatment needed, a total of 177 Saudi males were examined. The average age was 31.25 years (±13.44) and 30.61 years (±10.21) for the surveyed and examined groups, respectively. Subjects' interest in orthodontic knowledge (25%) and demand (27.6%) were not significantly different (P = 0.113), unlike the highly significant difference in the need counterpart (62.5%, P < 0.001). Highly significant differences (P < 0.001) were detected between the three outcome frequencies (knowledge interest, demand, and need) within all dental disciplines, except for the endodontic group where there was no significant difference detected (P = 0.625). Further analysis for the differences between each possible pairing of the three outcomes is highlighted. CONCLUSIONS: Subjects' knowledge of orthodontics approximated their treatment demand. However, orthodontic need was significantly much higher. Different patterns of distinction for other dental specialties were detected and described.